PERLINDUNGAN HUKUM MEREK BATIK PADA PENGRAJIN BATIK GIRILAYU, MATESIH, KARANGANYAR - Zuliana Ayu Sholihah; Pranoto Pranoto (Fakultas Hukum Universitas Sebelas Maret, 2026)
Legal writing aims to find out the obstacles, solutions, implementation of trademark registration and legal protection among Girilayu Batik Craftsmen. The empirical research is descriptive in nature with the location of Girilayu village, Matesih district, Karanganyar regency. Data collection techniques used interviews and collection of legal materials. Qualitative data analysis techniques. The results of the study explain the obstacles for Girilayu Batik Craftsmen, namely non-normative barriers, the absence of information on brand rights and limited funds; normative barriers, long registration process. While the legal protection that the Girilayu Batik Craftsmen get is when they have registered and have issued a trademark certificate. Solutions for non-normative barriers, empowering SMEs of the Karanganyar Regional Government in the form of KI socialization, assisting the legalization of IP and brand consulting services. The solution to normative barriers is the revision of Law Number 20 of 2016 concerning Marks and Geographical Indications so that trademark registration is shorter.